2011
DOI: 10.1021/nn2023057
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Growth and Differentiation of Human Mesenchymal Stem Cells by the Arrangement of Individual Carbon Nanotubes

Abstract: Carbon nanotube (CNT) networks on solid substrates have recently drawn attention as a means to direct the growth and differentiation of stem cells. However, it is still not clear whether cells can recognize individual CNTs with a sub-2 nm diameter, and directional nanostructured substrates such as aligned CNT networks have not been utilized to control cell behaviors. Herein, we report that human mesenchymal stem cells (hMSCs) grown on CNT networks could recognize the arrangement of individual CNTs in the CNT n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
113
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(124 citation statements)
references
References 34 publications
(46 reference statements)
5
113
1
5
Order By: Relevance
“…[4] Their unique properties provide a tremendous potential for applications in fields as diverse as electronics, [5] aerospace industries, [6] sensors, [7] actuators, [8] or composites. [9] Based on their properties, researchers have also been exploring CNTs potential for biological and biomedical applications as drug delivery systems, [10] substrate for cells growth in tissue regeneration, [11] therapeutic cerasela-zoica …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Their unique properties provide a tremendous potential for applications in fields as diverse as electronics, [5] aerospace industries, [6] sensors, [7] actuators, [8] or composites. [9] Based on their properties, researchers have also been exploring CNTs potential for biological and biomedical applications as drug delivery systems, [10] substrate for cells growth in tissue regeneration, [11] therapeutic cerasela-zoica …”
mentioning
confidence: 99%
“…agents, [11] or as vectors for gene transfection. [12] Such broad applications of CNTs have led to an increased production level and thus increased concerns regarding human and environmental exposure.…”
mentioning
confidence: 99%
“…22 As an explanation for the enhanced proliferation and osteogenic differentiation, mechanotransduction pathways triggered by high cytoskeletal tension in the aligned hMSCs have been proposed. 23 Our results on vinculin gene expression on MWCNTs-TCP contribute to this direction. FAK and vinculin are major players in the focal adhesion processes activated by integrin-fibronectin interactions.…”
Section: Cell Spread On Mwcnts Toward a Polygonal Shape With Manymentioning
confidence: 64%
“…Previous studies found that the different micro-patterned ECM surface of biomaterial has a significant effect on the adsorption quantity of protein and life behavior of stem cells [25]. These results showed that micro-patterned size not only controls the adsorption quantity of bone growth factor protein, but also impacts on cell adhesion and morphology, as well as protein expression during the cell growth process [28]. Compared with un-micro-patterned plane biomaterials, micro-patterned surface can promote cells to secrete more type II collagen and type VI collagen, which indicates its role in regulation of cell growth [27]; On the other hand, even with the same size and shape of micro-pattern, different ECM protein micro-patterns have significant different effects on cell adhesion and protein expression.…”
Section: The Effect Of Surface Physical Propertiesmentioning
confidence: 82%